(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
Low feed grade affects meat quality parameters along with physiological condition of farm poultry. Due to the fact that many countries have abandoned the use of antibiotics, there is a need for further development and introduction of alternative preparations. An important role in this situation is occupied by the use of probiotics. According to the results of scientific research, the probiotic "Activil-3" had a positive effect on the meat quality of broiler chickens.